Universiti Malaysia Pahang and Aspen Technology to Build an Ecosystem of Knowledge Sharing - Cynthia, Ignatius (Reach Publishing Sdn Bhd., 2022)
The Faculty of Chemical and Process Engineering Technology (FTKKP) of Universiti Malaysia Pahang (UMP) and Aspen Technology (AspenTech) are collaborating to prepare graduates to meet industry demand in the field of chemical and process engineering technology.